Computational fluid dynamics evaluations on new designs of the delta-shaped blade Darrieus hydrokinetic turbine - Tantichukiad, K.; Yahya, A.; Mustafah, A.M.; Rafie, A.S. Mohd; Su, A.S. Mat (Universiti Malaysia Pahang, 2024)
In this research, the computational fluid dynamics (CFD) approaches using ANSYS Fluent solver was employed to evaluate new designs of the delta-shaped bladed Darrieus hydrokinetic turbines (DHKT) employing NACA0012 hydrofoils. The 2-bladed models with four different designs (MD1-MD4) of varying blade characteristics and cross-sectional areas were simulated. The models were positioned fully submerged inside a water flow domain and were forced to rotate with different rotational speeds by utilizing the sliding mesh technique under a constant upstream velocity of 1.5 m/s. The results using a Shear Stress Transport (SST) k-ω turbulence model were compared with previous studies. The optimum model designs were shown to be the models with twisted blades and reduced and constant cross-sectional areas (MD3 and MD4). The 3-bladed models with similar blade characteristics (MD7 and MD8) were continuously tested and compared with the 2-bladed models. The 2-bladed models performed better during the higher range of tip speed ratio (λ), whereas 3-bladed models were outstanding at the lower range. Based on the work using CFD approaches in this paper, the MD4 model was shown to be the most appropriate design to operate under the specified conditions.